Structure,morphologyandopticalpropertiesofundopedand MN-doped ZnO(1 x)Sx nano-powderspreparedbyprecipitation method - Wako, Ali Halake; Dejene, F. B.; Onani, M. O .; Koao, L. F.; Motloung, S. V.; Yihunie, M. T. (Elsevier, 2015)
The undopedandMn-dopedZnO(1 x)Sx nano-powders weresuccessfullysynthesizedbyprecipitation method withoutusinganycappingagent.Itsstructure,morphology,elementalanalysis,opticaland luminescence propertiesweredeterminedbyscanningelectronmicroscopy(SEM),energy-dispersive X-rayspectroscopy(EDS),UV–vis spectroscopy(UV)andphotoluminescencespectroscopy(PL).Atypical SEM imageoftheun-dopedZnO(1 x)Sx nanoparticles exhibit flake likestructuresthatchangestonearly spherical particleswithMn-doping.TheXRDofundopedandMndopedZnO(1 x)Sx patternrevealsthe formation ofaproductindexedtothehexagonalwurtzitephaseofZnS.Thenanopowdershavecrys- tallite sizesestimatedfromXRDmeasurementswereintherangeof10–20 nm.Allthesamplesshowed absorption maximumofZnO(1 x)Sx at 271nmandhightransmittanceinUVandvisibleregion,re- spectively.TheundopedZnO(1 x)Sx nanoparticles showstrongroom-temperaturephotoluminescence with fouremissionbandscenteringat338nm,384nm,448nmand705nmthatmayoriginatetothe impurity ofZnO(1 x)Sx, existenceofoxiderelateddefects.Thecalculatedbandgapofthenanocrystalline ZnO(1 x)Sx showedablue-shiftwithrespecttotheMn-doping.ThePLspectraoftheMn-dopedsamples exhibitastrongorangeemissionataround594nmattributedtothe 4T1–6A1 transitionoftheMn2þ ions.
TheauthorssendimmensegratitudetotheSouthAfrica'sNa- tionalResearchFoundation(NRF),theUniversityoftheFreeState physicsdepartmentandtheOrganizationfortheProhibitionof ChemicalWeapons(OPCW)forthe financialassistanceforthis study.
Keywords: Zinc oxide; Precipitation; Doping; Photoluminescence; Nanomaterials